Genetic markers in a Malaysian population: variants of uridine monophosphate kinase (UMPK), phosphoglycolate phosphatase (PGP) and pancreatic amylase (AMY₂) - K. H., Zarinah; Abdullah, F.; Tan, S. G. (Informa Healthcare, 1984)
Three genetic markers, red-cell UMPK, PGP and serum AMY₂ were investigated in Malaysians of Malay, Chinese and Indian ancestries using starch-gel and agarose-gel electrophoresis. UMPK was found to be polymorphic in all three races. Variants were observed for PGP in Malays; in Indians it is a polymorphic marker whereas it is monomorphic in Chinese. AMY₂ was polymorphic only in Indians. The UMPK¹ frequencies in Malays, Chinese and Indians, respectively, are 0.851, 0.880 and 0.942. The PGP¹ frequencies are 0.991, 1.000, 0.962, and the AMY½frequencies are 1.000, 1.000 and 0.983.